A nova gest?o p?blica da escola em Feira de Santana-BA: implica??es pol?ticas e pedag?gicas (2000-2013) - Rozzato, Katia Danielle Santos Silva (2020)
This research discusses the school management and its possible influences onpedagogical work in public municipal schools of Feira de Santana in the period of 2000 to 2013. The study was guided by the following question: What is the modus operandi of the principle of democratic management of education in the municipality of Feira de Santana and what are its repercussions at school, especially as regards the relationship between the admission of the principal?s role and the processes of organization and development of pedagogical work? The general objective was to characterize and analyze the modus operandi of the democratic management of education in the municipality of Feira de Santana and its repercussions at school, with emphasis on the analysis of the relations between the provision of the role of school principal and the organization and development of pedagogical work, in the period from 2000 to 2013. The research was referenced by a qualitative approach and treated the collected data based on the content analysis, according to Bardin (2016) and Amado (2013). The analytical categories that guided the study were: democratic management, participation and the organization of pedagogical work, taking as a general assumption the notion of democracy, inspired by Chau? (1997), which is conceived as a political form based on three fundamental rights: equal rights; freedom of thought and expression; and participation in power. Combined with this conception, the organization of educational management was taken in an emancipatoryperspective, based on Freire (2014), Paro (2016, 2002), Paiva (1987) and Lib?neo (2004). Sources for the empirical body were taken from printed documents from the public agencies and public institutions responsible for the planning of national and municipal education, as well as for the two schools that were the empirical field; a digital questionnaire aimed at characterizing the profile of school managers from the municipality; and semi-structured interviews conducted with two female school principals, three parents, two female employees and two female teachers from the researched schools. The collected data allows to say that the education laws of Feira de Santana and the actions based on them are representative of two distinct moments: from 1987 to 1994 presents an emancipatory bias and after this period has undergone changings that demonstrate a progressive alignment with the liberal conception and, therefore, they reflect the models of the new public management in education. This movement since the year 2000 has been producing the emptying of the political function of the participation?s mechanisms, making it difficult to achieve the principle of democratic management in municipal schools in Feira de Santana.